Alienation and Hopes in Indonesian Migrant Worker Literature Work - Madrah, Muna Yastuti; Praptawati, Destary (Celt: A Journal of Culture, English Language Teaching & Literature, 2021)
Abstract: Female Indonesian migrant domestic workers (DMWs) often get a negative predicate both in Indonesia and in destination countries. For example, DMWs in Singapore are treated unequally by Singaporean society, in Indonesia, as well, their work is seen as a lowly job. They can be categorized as a marginal group. Marginals are marginalized people whose rights are ruled out by people that have power. Hence, they find it difficult to adapt to their environment and they are always suppressed. The circumstances lead to the feeling of alienation for DMWs. The alienation they have experienced is often ignored as a reality of the life of migrant workers. This study takes the object of poetry by Female Indonesian DMWs in Singapore. It explores how marginalization and alienation are expressed in literary work by female domestic migrant workers. This study, also analyzes how the expression of literary work can be functioned as a medium to voice alienation and to overcome its problem. This research used textual analysis, including the application of semiotics and narratology to see the marginalization and alienation faced by the migrant workers which are represented through a literary work. As complementary data, virtual interviews with the author of poetry was conducted.